Stereotypical Colours in European Gender Statistics Visualisations - Mojca Bavdaž; Jerneja Kos; Tamara Trošt; Denis Marinšek (SAGE Open)
Gender statistics play an important role in highlighting gender inequalities, but they are often presented in a conventional way by depicting males in blue and females in pink. Using stereotypical colours saves users from having to learn which colour is used for which gender. However, colours can also convey unintended messages of strength vs. weakness, status, and power, confirming the very stereotypes they are intended to address. National statistical institutes have the opportunity to influence public perceptions and could play a leading role in raising awareness about gender issues. In our article, we examine the use of colours to represent gender in the Twitter accounts (rebranded to X accounts on July 23, 2023) of national statistical institutes in 24 European countries. Quantitative analysis of 631 colour pairs from 644 images reveals that the stereotypical use of colours in official statistics is still widespread. We examine the nine patterns discovered and comment on possible solutions.